Corporate crisis management in Italy: execution, monitoring and performance analysis of recovery business and financial plans. (2018) - Tron, Alberto; Valenza, Giuseppe; Caputo, Andrea
This paper presents a thorough investigation of how corporate crises are managed in the Italian context. It offers an investigation of the legal, accounting, finance and managerial aspects that are involved in the formal resolution of the crisis. The paper adopts a qualitative methodology consisting in a critical review of both the academic and the practical literature to present a systematic overview of how recovery plans are executed, monitored and their performance analysed. The paper presents important insights for researchers, practitioners, entrepreneurs and managers interested in crisis management.